2021
DOI: 10.1017/s136898002100001x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to food-based dietary guidelines among adolescents in Germany according to socio-economic status and region: results from Eating Study as a KiGGS Module (EsKiMo) II

Abstract: Objective: Dietary habits developed during childhood and adolescence are likely to continue into adulthood. An unbalanced diet may cause nutrient deficiencies and excessive energy intake; these enhance the risk for developing overweight and obesity and their co-morbidities. In the present analysis, food consumption of adolescents is described and evaluated against German food-based dietary guidelines with special focus on socio-economic status (SES) and region of residence. Design: Withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…In fact, almost 50% of students consumed insufficient amounts of fruit and vegetables, less than 60% ate legumes and fish regularly, and more than 80% consumed meat and meat products more than once a day. Similar data were recently reported across EU countries in the latest Health at Glance Report 2020 [ 29 ] and in the Eating Study as a KiGGS Module (EsKiMo) II, conducted on 1353 adolescents aged 15–17 years [ 30 ]. Notably, only one in nine adolescents reported eating five or more servings of fruit and vegetables per day, while meat consumption was well above recommendations.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, almost 50% of students consumed insufficient amounts of fruit and vegetables, less than 60% ate legumes and fish regularly, and more than 80% consumed meat and meat products more than once a day. Similar data were recently reported across EU countries in the latest Health at Glance Report 2020 [ 29 ] and in the Eating Study as a KiGGS Module (EsKiMo) II, conducted on 1353 adolescents aged 15–17 years [ 30 ]. Notably, only one in nine adolescents reported eating five or more servings of fruit and vegetables per day, while meat consumption was well above recommendations.…”
Section: Discussionsupporting
confidence: 79%
“…Since the focus is on foods and diet quality rather than the effect of single nutrients on health, understanding how diet quality is associated with socio-demographics and micronutrients intake has become relevant to nutrition research [11][12][13]. However, there is a gap in research that has been undertaken in low-and middle-income countries, including LA countries.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-country surveys provide important information on health behaviors of a population and sub-groups. Information including inadequacy of dietary intake in certain population groups is needed to identify relevant fields of action for public health policies and behavioral-change interventions [ 13 ]. The Latin American Health and Nutrition Study (acronym in Spanish and Portuguese, ELANS) [ 14 ] provides an opportunity to understand these gaps.…”
Section: Introductionmentioning
confidence: 99%
“…Having overweight/obese directly depends on the social and economic status of a population [20] , [21] . It is indeed true, as our study results have shown that GDP as an indicator of an economic status of a country directly influences the increase in a population of people with overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%